POLICY OF MANAGEMENT OF THE HOUSEHOLD BUDGET - YASYSHENA, Valentyna; DOLIUK, Alla; YAROVA, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The habit of effectively managing one’s finances and the ability to properly allocate one’s funds is the key to economic stability for both an individual and the state as a whole. In the modern world, households play an important role as an economic entity, the well-being of the entire country depends on the results of its activities. Households are the only socio-economic entity within which the process of reproduction of the population, formation and education of the individual takes place. The recognition of households as equal participants in financial relations contributed to the emergence of a number of problems related to the peculiarities of income formation and spending in the conditions of transformational changes in the economy of Ukraine. The scientific article is devoted to research in the field of household finances. This topic is becoming more and more relevant in the modern world. The article reveals the essence of the concept of "household", highlights the main characteristics of households, the concept and functions of the household budget, and considers the types of household budgets. In particular, the article considers types of household income, classification of household expenses. The structure of family budget planning is presented. The main rules of managing budget funds are highlighted. Approaches to the competent distribution of money are disclosed.It has been established that a key aspect of household budget management is responsibility for one’s finances and making decisions that reflect needs and goals. Regardless of how you manage your personal finances, the main thing is that only increasing your level of financial literacy will help you achieve personal well-being and learn how to properly allocate your funds across all expenditure items. A person must be constantly improving, analyzing his expenses in order to optimize them, while introducing new methods of obtaining income, learning to invest and manage his funds.